The complete chloroplast genome of Walla Patta, Gyrinops walla Thymelaeaceae, an agarwood-producing tree species from Sri Lanka - Chen, Jingrui; Lee, Shiou Yih; Munugoda, K. D.; Mohamed, Rozi; Subasinghe, S. M. C. U. P.; Liao, Wenbo (Taylor & Francis, 2021)
Gyrinops walla is an important agarwood-producing tree and threatened species from Sri Lanka. Herein, we assembled and characterized the complete chloroplast (cp) genome of G. walla as a genomic resource for conservation purposes. The 175,130 bp long genome is comprised of 87,376 bp large single-copy (LSC) and 3316 bp small single-copy (SSC) regions, which are separated by two inverted repeat (IR) region, each with a size of 42,291 bp. A total of 140 genes were predicted for the cp genome, which includes 94 protein-coding, 38 tRNA, and eight rRNA genes. Phylogenetic analysis showed that G. walla is fully resolved in a sister position to Aquilaria in the family Thymelaeaceae. The data provided will be useful for study on the molecular phylogenetics and evolution of Thymelaeaceae in the future.